Traffic burden at Skudai Toll Plaza: an analysis using complex network - M. Asrah, N.; Djauhari, M. A.; Mohamad, I. (Penerbit UTHM, 2018)
One of the most important elements for the overall economic development in any country all over the world is road development. When the roads have a better interconnected network, it will help the economic activities such as trade to increase. As a country develop, the demand for efficient road transportation will get increase and highways are required to meet this increased demand. In Malaysia, the development of highway is part of government commitment to ensure economic growth of economic so that it will improve the quality of life in the society. Projek Lebuhraya Usahasama Berhad (PLUS) is one of the highway operators in Malaysia. It is also the largest highway concessionary or build–operate–transfer (BOT) operator company in Malaysia. In this paper, the traffic burden of Skudai toll plaza is studied by considering all PLUS toll plazas as a complex network. The data used is based on the number of vehicles entering from each PLUS toll plazas to Skudai and exiting from Skudai to other PLUS toll plazas. The data analysis is based on the measure of similarity among toll plazas along PLUS highway where Skudai toll plaza as the origin and destination. The interrelationships amongst toll plazas are studied by using minimum spanning tree (MST). The interpretation of MST is conducted by using centrality measures usually used in Social Network Analysis. Further, this study will provide some recommendations related to traffic highway development.